Flat non-aqueous electrolyte battery
By using a conductive layer with a metal member with an elastic part and a carbon main component in the nonaqueous electrolyte battery, the crack problem and high internal resistance of the positive electrode mold mixture are solved, and better battery performance is achieved.
Patent Information
- Application Number
- JP2020187039
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-10
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2040-11-10
AI Technical Summary
The prior art is difficult to effectively suppress cracks in the positive electrode mold mixture while reducing the internal resistance of the nonaqueous electrolyte battery.
In the non-aqueous electrolyte battery, a metal member with an elastic part is used, and a conductive layer of a carbon main component is arranged on the side of the positive electrode cover, and the metal member is located between the conductive layer and the positive electrode cover.
It effectively suppresses cracks in the positive electrode mold mixture, while reducing the internal resistance of the non-aqueous electrolyte battery and improving the performance of the battery.
Smart Images

Figure 0007657573000003 
Figure 0007657573000001 
Figure 0007657573000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a flat nonaqueous electrolyte battery capable of reducing internal resistance while suppressing cracking of a positive electrode having a molded body of a positive electrode mixture. [Background technology]
[0002] Flat nonaqueous electrolyte batteries, which are configured by housing a laminated electrode body having a positive electrode and a negative electrode in an exterior body having a positive electrode can and a negative electrode can, and which use a positive electrode having a molded body (pellet, positive electrode mixture layer, etc.) of a positive electrode mixture containing a positive electrode active material and the like, are currently widely used in the form of primary batteries or secondary batteries.
[0003] In general, the positive electrode can and the negative electrode can that constitute the exterior body of a flat nonaqueous electrolyte battery function as current collectors by having their inner surfaces in contact with the positive electrode and the negative electrode.
[0004] In the flat non-aqueous electrolyte battery described above, the negative electrode shrinks with discharge in the case of a primary battery, and expands and shrinks with charge and discharge in the case of a secondary battery. When the negative electrode shrinks with discharge of the battery, the electrical connection with the inner surface of the negative electrode can becomes insufficient, and the capacity that the battery originally has may not be fully utilized.
[0005] Although not intended to solve the current collection problem caused by the shrinkage of the negative electrode accompanying the discharge of the battery, Patent Document 1 proposes a technique of placing a conductive carbon sheet or the like between the negative electrode can and the negative electrode. Depending on the degree of shrinkage of the negative electrode accompanying the discharge, the action of the carbon sheet may be able to maintain the electrical connection between the negative electrode and the inner surface of the negative electrode can to some extent. However, in batteries in which the negative electrode shrinks significantly during discharge, the electrical connection between the negative electrode and the inner surface of the negative electrode can may become insufficient, leaving room for improvement.
[0006] On the other hand, as described in the above Patent Document 1, for example, a spring is arranged in a compressed state between the positive electrode and the positive electrode can, and when the negative electrode shrinks, the spring's restoring force presses the negative electrode against the inner surface of the negative electrode can from the positive electrode side, thereby making good contact with the inner surface of the negative electrode can even if the negative electrode shrinks. However, when used in a battery in which the negative electrode shrinks significantly due to discharge, if a spring with a large restoring force is used to sufficiently maintain contact between the negative electrode and the negative electrode can due to the shrinkage, there is a problem that cracks occur in the molded body of the positive electrode mixture, reducing the battery capacity. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-212130 A (Claim 1,
[0024] ,
[0033] , Figure 1, etc.) Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a flat nonaqueous electrolyte battery that can reduce internal resistance while suppressing cracking of a positive electrode having a molded body of a positive electrode mixture. [Means for solving the problem]
[0009] The flat nonaqueous electrolyte battery of the present invention is characterized in that a laminated electrode body having a positive electrode and a negative electrode is housed in an exterior body having a positive electrode can and a negative electrode can, the positive electrode has a molded body of a positive electrode mixture containing a positive electrode active material, a conductive layer mainly composed of carbon is disposed on the positive electrode can side of the positive electrode, and a metal member having an elastic portion is disposed between the positive electrode can and the conductive layer mainly composed of carbon.
[0010] In the battery industry, flat batteries whose diameter is greater than their height are called coin batteries or button batteries, but there is no clear difference between coin batteries and button batteries, and the flat nonaqueous electrolyte battery of the present invention includes both coin batteries and button batteries. Effect of the Invention
[0011] According to the present invention, it is possible to provide a flat nonaqueous electrolyte battery capable of reducing the internal resistance while suppressing cracking of a positive electrode having a molded body of a positive electrode mixture. [Brief description of the drawings]
[0012] [Figure 1] 1 is a cross-sectional view that illustrates a schematic diagram of an example of a flat nonaqueous electrolyte battery of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Fig. 1 is a cross-sectional view showing a schematic example of a flat nonaqueous electrolyte battery of the present invention. In the flat nonaqueous electrolyte battery 1 shown in Fig. 1, a laminated electrode body having a positive electrode 10 and a negative electrode 20 is enclosed in an exterior body formed of a positive electrode can (exterior can) 40, a negative electrode can (sealing can) 50, and a gasket 60 interposed between them. A separator 30 is usually interposed between the positive electrode 10 and the negative electrode 20, but when the flat nonaqueous electrolyte battery 1 is a solid electrolyte battery, a solid electrolyte layer 30 is interposed between the positive electrode 10 and the negative electrode 20 instead of the separator.
[0014] The negative electrode can 50 is fitted into the opening of the positive electrode can 40 via a gasket 60, and the open end of the positive electrode can 40 is tightened inward, whereby the gasket 60 comes into contact with the negative electrode can 50, sealing the opening of the positive electrode can 40 and forming a sealed structure inside the battery. In the flat nonaqueous electrolyte battery 1, the positive electrode can 40 also serves as a positive electrode terminal, and the negative electrode can 50 also serves as a negative electrode terminal. In the flat nonaqueous electrolyte battery 1 shown in FIG. 1, the exterior can is the positive electrode can 40 and the sealing can is the negative electrode can 50, but in the flat nonaqueous electrolyte battery of the present invention, the sealing can can be the positive electrode can and the exterior can can be the negative electrode can.
[0015] 1, the positive electrode 10 has a molded body of a positive electrode mixture containing a positive electrode active material, etc. A conductive layer 70 mainly composed of carbon is disposed on the positive electrode can 40 side of the positive electrode 10, and further, a metal member 80 having an elastic portion is disposed between the positive electrode can 40 and the conductive layer 70 mainly composed of carbon.
[0016] In this way, the flat nonaqueous electrolyte battery of the present invention has a laminated electrode assembly including a positive electrode having a molded body of a positive electrode mixture containing a positive electrode active material and a negative electrode housed in an exterior body having a positive electrode can and a negative electrode can, a conductive layer mainly composed of carbon is disposed on the positive electrode can side, and a metal member having an elastic portion is disposed between the positive electrode can and the conductive layer mainly composed of carbon.
[0017] In the flat nonaqueous electrolyte battery of the present invention, even if the negative electrode shrinks due to discharge, the negative electrode is pressed against the inner surface of the negative electrode can from the positive electrode side by the action of the metal member having an elastic part arranged on the positive electrode side, so that the electrical connection between the negative electrode and the inner surface of the negative electrode can is maintained well, and the internal resistance can be maintained low. In addition, a conductive layer mainly composed of carbon is arranged between the positive electrode and the metal member having an elastic part, so that even if stress is applied to the positive electrode by the restoring force of the metal member having an elastic part, the conductive layer mainly composed of elastically deformable carbon plays the role of a cushion, and the occurrence of cracks in the positive electrode (the molded body of the positive electrode mixture) can be suppressed.
[0018] Furthermore, when the positive electrode and the metal member having the elastic portion are in direct contact with each other, the electrical connection between them is likely to be insufficient. However, by interposing a conductive layer between them that is mainly composed of carbon and has a wide range of work functions, the electrical connection between the positive electrode and the metal member having the elastic portion can be made good.
[0019] In the flat nonaqueous electrolyte battery of the present invention, the above-mentioned functions make it possible to suppress cracking of the positive electrode mixture compact and to reduce the internal resistance.
[0020] The flat nonaqueous electrolyte battery of the present invention includes a primary battery and a secondary battery. The flat nonaqueous electrolyte battery of the present invention also includes a battery using a nonaqueous electrolyte such as a nonaqueous electrolyte solution (nonaqueous electrolyte primary battery, nonaqueous electrolyte secondary battery) and a solid electrolyte battery having a solid electrolyte layer interposed between a positive electrode and a negative electrode (solid electrolyte primary battery, solid electrolyte secondary battery).
[0021] (Carbon-based conductive layer) In a flat nonaqueous electrolyte battery, the conductive layer mainly composed of carbon and arranged on the positive electrode can side of the positive electrode may be, for example, a conductive layer containing carbon as a main component and also containing a binder or the like.
[0022] In the case of a conductive layer containing carbon and a binder, the carbon is preferably fibrous carbon such as carbon fiber, carbon nanotube, vapor grown carbon fiber, etc., and the binder is preferably styrene butadiene rubber, nitrile rubber, etc.
[0023] In the conductive layer containing carbon and a binder, carbon is the main component, and the carbon content is preferably more than 50 mass% (more preferably 70 mass% or more) and 99 mass% or less. Also, the binder content in the conductive layer containing carbon and a binder is preferably 1 mass% or more and less than 50 mass% (more preferably 30 mass% or less).
[0024] The conductive layer containing carbon and a binder can be formed, for example, by applying a conductive layer-forming composition prepared by dispersing carbon and a binder in water or an organic solvent (the binder may be dissolved) onto the surface of a positive electrode and drying the composition.
[0025] In addition, for the conductive layer mainly composed of carbon, various carbon sheets, for example, porous carbon sheets composed of fibrous carbon such as carbon paper, carbon cloth, and carbon felt, can be preferably used, and the conductive layer can be formed by disposing these carbon sheets on the positive electrode can side of the positive electrode (the carbon sheet and the positive electrode do not need to be bonded to each other, but may be bonded to each other).
[0026] These carbon sheets may have a single layer structure, a multilayer structure in which carbon papers are laminated together, carbon cloths are laminated together, or carbon felts are laminated together, or a multilayer structure in which two or more of carbon papers, carbon cloths, and carbon felts are laminated together.
[0027] Taking into consideration electrical conductivity and the like, the fiber diameter of the fibrous carbon constituting the porous carbon sheet is preferably 2 to 30 μm.
[0028] The thickness of the conductive layer mainly composed of carbon is preferably 10 μm or more, more preferably 50 μm or more, from the viewpoint of suppressing the occurrence of cracks in the molded body of the positive electrode mixture due to the action of the metal member having an elastic portion. Also, from the viewpoint of reducing the occupancy rate of the conductive layer mainly composed of carbon in the battery volume and making the thickness of the electrode as large as possible, thereby making it possible to increase the battery capacity, the thickness of the conductive layer mainly composed of carbon is preferably 200 μm or less, more preferably 100 μm or less.
[0029] (Metal member having elastic portion) In a flat nonaqueous electrolyte battery, the metal member having an elastic part disposed between the positive electrode can and the conductive layer mainly composed of carbon is made of a conductive metal, preferably stainless steel. Note that the "metal member having an elastic part" according to the present invention is not required to be elastic in its entirety, but it is sufficient that it has a part having an elasticity (i.e., an elastic part) that can press the negative electrode of the laminated electrode body against the inner surface of the negative electrode can from the positive electrode side.
[0030] The metal member having an elastic portion used in a flat nonaqueous electrolyte battery preferably has a restoring force of at least half the thickness of the negative electrode, and more preferably at least equal to the thickness of the negative electrode.
[0031] Specific examples of metal members having an elastic portion include springs such as leaf springs (thin leaf springs, disc springs, etc.), wave washers, and coil springs; retaining rings; and the like.
[0032] (positive electrode) The positive electrode of the flat nonaqueous electrolyte battery is composed of a molded body of a positive electrode mixture, and examples of the positive electrode of the flat nonaqueous electrolyte battery include a positive electrode mixture composed of only a molded body of a positive electrode mixture and a positive electrode mixture layer formed on a current collector.
[0033] When the flat non-aqueous electrolyte battery is a primary battery, the same positive electrode active material as that used in the conventionally known non-aqueous electrolyte primary battery can be used. Specifically, for example, manganese dioxide, lithium-containing manganese oxide (e.g., LiMn3O6, or a composite oxide having the same crystal structure as manganese dioxide (β-type, γ-type, or a structure in which β-type and γ-type are mixed, etc.) and a Li content of 3.5 mass% or less, preferably 2 mass% or less, more preferably 1.5 mass% or less, particularly preferably 1 mass% or less, etc.), Li a Ti 5 / 3 Examples include lithium-containing composite oxides such as O4 (4 / 3≦a<7 / 3); vanadium oxide; niobium oxide; titanium oxide; sulfides such as iron disulfide; graphite fluoride; silver sulfides such as Ag2S; and nickel oxides such as NiO2.
[0034] In addition, when the flat nonaqueous electrolyte battery is a secondary battery, the same positive electrode active material as that used in conventionally known nonaqueous electrolyte secondary batteries, that is, the same active material capable of absorbing and releasing Li (lithium) ions, can be used. 1-x M r Mn 2-rO4 (where M is at least one element selected from the group consisting of Li, Na, K, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Zr, Fe, Co, Ni, Cu, Zn, Al, Sn, Sb, In, Nb, Ta, Mo, W, Y, Ru, and Rh; 0 ≦ x ≦ 1, 0 ≦ r ≦ 1), a spinel-type lithium manganese composite oxide, Li r Mn (1-s-t) Ni s M t O (2-u) F v (where M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr, and W; 0 ≦ r ≦ 1.2, 0 < s < 0.5, 0 ≦ t ≦ 0.5, u + v < 1, -0.1 ≦ u ≦ 0.2, 0 ≦ v ≦ 0.1), a layered compound, Li 1-x Co 1-r M r O2 (where M is at least one element selected from the group consisting of Al, Mg, Ti, V, Cr, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba; 0 ≦ x ≦ 1, 0 ≦ r ≦ 0.5), a lithium cobalt composite oxide, Li 1-x Ni 1-r M r O2 (where M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba; 0 ≦ x ≦ 1, 0 ≦ r ≦ 0.5), a lithium nickel composite oxide, Li 1+s-x M 1-r N r PO4F s (where M is at least one element selected from the group consisting of Fe, Mn, and Co; N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba; 0 ≦ x ≦ 1, 0 ≦ r ≦ 0.5, 0 ≦ s ≦ 1), an olivine-type composite oxide, Li 2-x M 1-r N rExamples of such compounds include pyrophosphate compounds represented by the formula: P2O7 (wherein M is at least one element selected from the group consisting of Fe, Mn, and Co, and N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba, and 0≦x≦2, 0≦r≦0.5), and the like. Among these compounds, only one may be used, or two or more may be used in combination.
[0035] When the flat nonaqueous electrolyte battery is a solid electrolyte secondary battery, the average particle size of the positive electrode active material is preferably 1 μm or more, more preferably 2 μm or more, and preferably 10 μm or less, more preferably 8 μm or less. The positive electrode active material may be primary particles or secondary particles formed by agglomeration of primary particles. When a positive electrode active material having an average particle size in the above range is used, a large interface with the solid electrolyte contained in the positive electrode can be obtained, and the load characteristics of the battery are further improved.
[0036] The average particle diameter of various particles (positive electrode active material, solid electrolyte, etc.) in this specification is the 50% diameter value (D) in the volume-based integrated fraction when calculating the integral volume from small particles using a particle size distribution measurement device (such as the Microtrac particle size distribution measurement device "HRA9320" manufactured by Nikkiso Co., Ltd.). 50 )
[0037] When the flat nonaqueous electrolyte battery is a solid electrolyte secondary battery, the positive electrode active material preferably has a reaction suppression layer on its surface for suppressing reaction with the solid electrolyte contained in the positive electrode.
[0038] If the positive electrode active material and the solid electrolyte come into direct contact with each other in the positive electrode mixture compact, the solid electrolyte may oxidize to form a resistance layer, which may reduce the ionic conductivity in the compact. By providing a reaction suppression layer that suppresses the reaction with the solid electrolyte on the surface of the positive electrode active material and preventing direct contact between the positive electrode active material and the solid electrolyte, it is possible to suppress the reduction in the ionic conductivity in the compact due to the oxidation of the solid electrolyte.
[0039] The reaction suppression layer may be made of a material that has ion conductivity and can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of materials that can form the reaction suppression layer include oxides containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti, and Zr, more specifically, Nb-containing oxides such as LiNbO3, Li3PO4, Li3BO3, Li4SiO4, Li4GeO4, LiTiO3, LiZrO3, Li2WO4, and the like. The reaction suppression layer may contain only one of these oxides, or may contain two or more of them, and further, a plurality of these oxides may form a composite compound. Among these oxides, it is preferable to use an Nb-containing oxide, and it is more preferable to use LiNbO3.
[0040] The reaction suppression layer is preferably present on the surface in an amount of 0.1 to 1.0 part by mass per 100 parts by mass of the positive electrode active material, in order to effectively suppress the reaction between the positive electrode active material and the solid electrolyte.
[0041] Methods for forming a reaction suppression layer on the surface of a positive electrode active material include the sol-gel method, the mechanofusion method, the CVD method, the PVD method, and the ALD method.
[0042] The content of the positive electrode active material in the positive electrode mixture is preferably 60 to 98 mass %.
[0043] The positive electrode mixture may contain a conductive assistant. Specific examples include carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofiber, and carbon nanotubes. For example, when Ag2S is used as the active material, conductive Ag is generated during the discharge reaction, so that the conductive assistant does not need to be contained. When the positive electrode mixture contains a conductive assistant, the content is preferably 1 to 10 mass%.
[0044] The positive electrode mixture may contain a binder. Specific examples of such binders include fluororesins such as polyvinylidene fluoride (PVDF). In addition, the positive electrode mixture may not contain a binder if good moldability can be ensured in forming a positive electrode mixture compact without using a binder, such as when a sulfide-based solid electrolyte is contained in the positive electrode mixture (described in detail later).
[0045] When the positive electrode mixture requires a binder, the content is preferably 15% by mass or less, and more preferably 0.5% by mass or more. On the other hand, when the positive electrode mixture contains a sulfide-based solid electrolyte and thus can obtain formability without the need for a binder, the content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0% by mass (i.e., no binder is contained).
[0046] When the flat nonaqueous electrolyte battery is a solid electrolyte battery, the positive electrode mixture contains a solid electrolyte. The solid electrolyte is not particularly limited as long as it has lithium ion conductivity, and examples of the solid electrolyte that can be used include sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes.
[0047] Examples of sulfide-based solid electrolytes include particles of Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, and Li2S-B2S3-based glass. In addition, thio-LISICON-type electrolytes [Li 10 GeP2S 12 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 Li 12-12a-b+c+6d-e M 1 3+a-b-c-d M 2 b M 3 c M 4 d M 512-e X e (provided that M 1 is Si, Ge or Sn, M 2 is P or V, M 3 is Al, Ga, Y or Sb, M 4 is Zn, Ca, or Ba, M 5 is either S or S and O, X is F, Cl, Br or I, 0 ≦ a < 3, 0 ≦ b + c + d ≦ 3, 0 ≦ e ≦ 3), or an argyrodite-type one [such as Li6PS5Cl, Li 7-f+g PS 6-x Cl x+y (provided that 0.05 ≦ f ≦ 0.9, -3.0f + 1.8 ≦ g ≦ -3.0f + 5.7), Li 7-h PS 6-h Cl i Br j (provided that h = i + j, 0 < h ≦ 1.8, 0.1 ≦ i / j ≦ 10.0), etc.] can also be used.
[0048] Examples of the hydride-based solid electrolyte include LiBH4, a solid solution of LiBH4 and the following alkali metal compound (for example, those having a molar ratio of LiBH4 to the alkali metal compound of 1:1 to 20:1). Examples of the alkali metal compound in the solid solution include at least one selected from the group consisting of lithium halides (such as LiI, LiBr, LiF, LiCl), rubidium halides (such as RbI, RbBr, RbF, RbCl), cesium halides (such as CsI, CsBr, CsF, CsCl), lithium amide, rubidium amide, and cesium amide.
[0049] Examples of the halide-based solid electrolyte include monoclinic LiAlCl4, defective spinel-type or layered-structured LiInBr4, monoclinic Li 6-3m Y m X6 (provided that 0 < m < 2 and X = Cl or Br), etc., and in addition, for example, those known from WO 2020 / 070958 and WO 2020 / 070955 can also be used.
[0050] As an example of an oxide-based solid electrolyte, there is garnet-type Li7La3Zr2O 12 , NASICON type Li 1+O Al 1+O Ti 2-O (PO4)3, Li 1+p Al 1+p Ge 2-p (PO4)3, perovskite-type Li 3q La 2 / 3-q Examples include TiO3.
[0051] Among these solid electrolytes, sulfide-based solid electrolytes are preferred due to their high lithium ion conductivity, sulfide-based solid electrolytes containing Li and P are more preferred, and argyrodite-type sulfide-based solid electrolytes, which have particularly high lithium ion conductivity and high chemical stability, are even more preferred.
[0052] From the viewpoint of reducing grain boundary resistance, the average particle size of the solid electrolyte is preferably 0.1 μm or more, and more preferably 0.2 μm or more, while from the viewpoint of forming a sufficient contact interface between the active material and the solid electrolyte, the average particle size is preferably 10 μm or less, and more preferably 5 μm or less.
[0053] The content of the solid electrolyte in the positive electrode mixture is preferably 4 to 40 mass %.
[0054] When a current collector is used for the positive electrode, the current collector can be made of a metal foil such as aluminum or stainless steel, a punched metal, a net, an expanded metal, a foamed metal, a carbon sheet, or the like.
[0055] The positive electrode mixture compact can be formed, for example, by compressing a positive electrode mixture prepared by mixing a positive electrode active material with a conductive assistant, a binder, a solid electrolyte, and the like, which are added as necessary, by pressure molding or the like.
[0056] In the case of a positive electrode having a current collector, the positive electrode can be produced by bonding a molded body of the positive electrode mixture formed by the above-mentioned method to the current collector by, for example, pressure bonding.
[0057] Alternatively, the positive electrode mixture may be mixed with a solvent to prepare a positive electrode mixture-containing composition, which may then be applied onto a substrate such as a current collector or a solid electrolyte layer (in the case of forming a solid electrolyte battery) that faces the positive electrode, dried, and then pressed to form a molded body of the positive electrode mixture.
[0058] The solvent for the positive electrode mixture-containing composition may be an organic solvent such as water or N-methyl-2-pyrrolidone (NMP). When the positive electrode mixture-containing composition also contains a solid electrolyte, it is preferable to select a solvent that does not easily deteriorate the solid electrolyte. In particular, since sulfide-based solid electrolytes and hydride-based solid electrolytes undergo chemical reactions due to a small amount of water, it is preferable to use a non-polar aprotic solvent represented by a hydrocarbon solvent such as hexane, heptane, octane, nonane, decane, decalin, toluene, or xylene. In particular, it is more preferable to use an ultra-dehydrated solvent with a water content of 0.001 mass% (10 ppm) or less. In addition, fluorine-based solvents such as "Vertrel (registered trademark)" manufactured by Mitsui DuPont Fluorochemicals, "Zeorolla (registered trademark)" manufactured by Nippon Zeon Co., Ltd., and "Novec (registered trademark)" manufactured by Sumitomo 3M Co., Ltd., as well as non-aqueous organic solvents such as dichloromethane and diethyl ether can also be used.
[0059] The thickness of the positive electrode mixture compact (in the case of an electrode having a current collector, the thickness of the positive electrode mixture compact per one side of the current collector; the same applies below) is usually 50 μm or more, but from the viewpoint of increasing the capacity of the battery, it is preferably 200 μm or more. Also, the thickness of the positive electrode mixture compact is usually 3000 μm or less.
[0060] In the case of a positive electrode produced by forming a positive electrode mixture layer made of a compact of a positive electrode mixture on a current collector using a positive electrode mixture-containing composition containing a solvent, the thickness of the positive electrode mixture layer is preferably 50 to 1000 μm.
[0061] (Negative electrode) The negative electrode of the flat nonaqueous electrolyte battery has a negative electrode mixture compact containing a negative electrode active material, a lithium sheet, or a lithium alloy sheet.
[0062] When the negative electrode is a molded body of a negative electrode mixture containing a negative electrode active material, examples of the negative electrode include a molded body (pellet, etc.) obtained by molding the negative electrode mixture, and a structure in which a layer (negative electrode mixture layer) made of a molded body of the negative electrode mixture is formed on a current collector.
[0063] When the negative electrode has a molded body of a negative electrode mixture, examples of the negative electrode active material include carbon materials such as graphite, simple substances containing elements such as Si and Sn, compounds (oxides, etc.), and alloys thereof, etc. In addition, lithium metal and lithium alloys (lithium-aluminum alloys, lithium-indium alloys, etc.) can also be used as the negative electrode active material.
[0064] The content of the negative electrode active material in the negative electrode mixture is preferably 10 to 99 mass %.
[0065] The negative electrode mixture may contain a conductive assistant. Specific examples thereof include the same conductive assistants as those exemplified above as those that may be contained in the positive electrode mixture. The content of the conductive assistant in the negative electrode mixture is preferably 1 to 10 mass%.
[0066] In addition, the negative electrode mixture may contain a binder. Specific examples thereof include the same binders as those exemplified above as those that may be contained in the positive electrode mixture. In addition, for example, in the case where a sulfide-based solid electrolyte is contained in the negative electrode mixture (described in detail later), if good moldability can be ensured in forming a compact of the negative electrode mixture without using a binder, the negative electrode mixture may not contain a binder.
[0067] When the negative electrode mixture requires a binder, the content is preferably 15% by mass or less, and more preferably 0.5% by mass or more. On the other hand, when the negative electrode mixture contains a sulfide-based solid electrolyte and thus can obtain formability without the need for a binder, the content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0% by mass (i.e., no binder is contained).
[0068] In the case where the flat nonaqueous electrolyte battery is a solid electrolyte battery, the negative electrode mixture contains a solid electrolyte. Specific examples thereof include the same solid electrolytes as those exemplified above as those that can be contained in the positive electrode mixture. Among the above-mentioned solid electrolytes, it is more preferable to use a sulfide-based solid electrolyte because it has high lithium ion conductivity and has a function of increasing the moldability of the negative electrode mixture.
[0069] The content of the solid electrolyte in the negative electrode mixture is preferably 4 to 49 mass %.
[0070] When a current collector is used in a negative electrode having a molded body of a negative electrode mixture, the current collector can be made of copper or nickel foil, punched metal, net, expanded metal, foamed metal; carbon sheet; or the like.
[0071] The negative electrode mixture compact can be formed, for example, by compressing a negative electrode mixture prepared by mixing a negative electrode active material, a conductive assistant, a solid electrolyte, a binder, etc., which are added as necessary, by pressure molding, etc. In the case of a negative electrode constituted only by a negative electrode mixture compact, it can be manufactured by the above-mentioned method.
[0072] In the case of a negative electrode having a current collector, the negative electrode can be produced by bonding a molded product of the negative electrode mixture formed by the above-mentioned method to the current collector by, for example, pressure bonding.
[0073] Furthermore, in the case of a negative electrode having a current collector, the negative electrode can also be produced by a method in which a negative electrode mixture-containing composition (paste, slurry, etc.) in which a negative electrode active material, and further a conductive assistant, a solid electrolyte, and a binder, which are added as necessary, are dispersed in a solvent, is applied to a current collector, dried, and then, as necessary, pressure molding such as calendaring is performed to form a molded body of the negative electrode mixture (negative electrode mixture layer) on the surface of the current collector.
[0074] As the solvent for the negative electrode mixture-containing composition, an organic solvent such as water or NMP can be used. When the negative electrode mixture-containing composition also contains a solid electrolyte, it is desirable to select a solvent that is unlikely to deteriorate the solid electrolyte. It is preferable to use the same solvent as the various solvents exemplified above as the solvent for the positive electrode mixture-containing composition containing a solid electrolyte.
[0075] The thickness of the negative electrode mixture compact (in the case of an electrode having a current collector, the thickness of the negative electrode mixture compact per one side of the current collector; the same applies below) is usually 50 μm or more, but from the viewpoint of increasing the capacity of the battery, it is preferably 200 μm or more. The thickness of the negative electrode mixture compact is usually 3000 μm or less.
[0076] In the case of a negative electrode produced by forming a negative electrode mixture layer made of a molded negative electrode mixture on a current collector using a negative electrode mixture-containing composition containing a solvent, the thickness of the negative electrode mixture layer is preferably 50 to 1000 μm.
[0077] In the case of a negative electrode having a lithium sheet or a lithium alloy sheet, one consisting of only this sheet or one consisting of this sheet laminated with a current collector is used.
[0078] Examples of alloying elements for the lithium alloy include aluminum, lead, bismuth, indium, and gallium, with aluminum and indium being preferred. The ratio of the alloying elements in the lithium alloy (when multiple alloying elements are included, the total ratio of the alloying elements) is preferably 50 atomic % or less (in this case, the balance is lithium and inevitable impurities).
[0079] In the case of a negative electrode having a lithium alloy sheet, a laminate is used in which a layer containing an alloying element for forming a lithium alloy is laminated on the surface of a lithium layer (a layer containing lithium) composed of a metallic lithium foil or the like, and the laminate is brought into contact with a non-aqueous electrolyte (such as a non-aqueous electrolyte solution) or a solid electrolyte in a battery to form a lithium alloy on the surface of the lithium layer, thereby forming a negative electrode. In the case of such a negative electrode, a laminate having a layer containing an alloying element on only one side of the lithium layer may be used, or a laminate having layers containing an alloying element on both sides of the lithium layer may be used. The laminate can be formed, for example, by pressing a metallic lithium foil and a foil composed of an alloying element.
[0080] The current collector can also be used when a lithium alloy is formed in a battery to form a negative electrode, and for example, a laminate having a lithium layer on one side of the negative electrode current collector and a layer containing an alloying element on the side of the lithium layer opposite the negative electrode current collector may be used, or a laminate having lithium layers on both sides of the negative electrode current collector and each lithium layer having a layer containing an alloying element on the side opposite the negative electrode current collector may be used. The negative electrode current collector and the lithium layer (metallic lithium foil) may be laminated by compression bonding or the like.
[0081] The layer containing the alloying elements in the laminate to be used as the negative electrode may be, for example, a foil composed of these alloying elements. The thickness of the layer containing the alloying elements is preferably 1 μm or more, more preferably 3 μm or more, and is preferably 20 μm or less, more preferably 12 μm or less.
[0082] The lithium layer of the laminate for use as the negative electrode may be, for example, a metallic lithium foil. The thickness of the lithium layer is preferably 0.1 to 1.5 mm. The thickness of the sheet of lithium or lithium alloy for the negative electrode is also preferably 0.1 to 1.5 mm.
[0083] In addition, when a negative electrode having a lithium sheet or a lithium alloy sheet has a current collector, the current collector can be the same as the current collector exemplified above as one that can be used for a negative electrode having a molded body of a negative electrode mixture.
[0084] (Solid electrolyte layer) When the flat nonaqueous electrolyte battery is a solid electrolyte battery (a solid electrolyte primary battery or a solid electrolyte secondary battery), a solid electrolyte layer is interposed between the positive electrode and the negative electrode.
[0085] The solid electrolyte constituting the solid electrolyte layer can be one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes exemplified above as those usable for the positive electrode. However, in order to improve the battery characteristics, it is preferable to contain a sulfide-based solid electrolyte, and it is more preferable to contain an Argyrodite-type sulfide-based solid electrolyte. And, it is even more preferable to contain a sulfide-based solid electrolyte in both the positive electrode and the solid electrolyte layer, and also in the negative electrode when the negative electrode is a molded body of a negative electrode mixture containing a solid electrolyte, and it is particularly preferable to contain an Argyrodite-type sulfide-based solid electrolyte.
[0086] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.
[0087] The solid electrolyte layer can be formed by a method of compressing a solid electrolyte by pressure molding or the like; a method of applying a composition for forming a solid electrolyte layer, which is prepared by dispersing a solid electrolyte in a solvent, onto a substrate, a positive electrode, or a negative electrode, drying the composition, and, if necessary, performing pressure molding such as pressing.
[0088] It is desirable to select a solvent that is unlikely to deteriorate the solid electrolyte as the solvent used in the solid electrolyte layer-forming composition, and it is preferable to use the same solvent as the various solvents exemplified above as the solvent for the positive electrode mixture-containing composition containing the solid electrolyte.
[0089] The thickness of the solid electrolyte layer is preferably 100 to 400 μm.
[0090] (Separator) When the flat nonaqueous electrolyte battery is a battery other than a solid electrolyte battery, the separator interposed between the positive electrode and the negative electrode should have sufficient strength and be capable of retaining a large amount of nonaqueous electrolyte. From this viewpoint, a microporous film or nonwoven fabric containing polyethylene, polypropylene, or an ethylene-propylene copolymer and having a thickness of 10 to 50 μm and an opening ratio of 30 to 70% is preferred.
[0091] (Non-aqueous electrolyte) In the case where the flat nonaqueous electrolyte battery is a battery other than a solid electrolyte battery, a nonaqueous liquid electrolyte (hereinafter, referred to as a "nonaqueous electrolyte") is usually used as the nonaqueous electrolyte. The nonaqueous electrolyte is obtained by dissolving an electrolyte salt such as a lithium salt in an organic solvent. The organic solvent is not particularly limited, but examples thereof include chain esters such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate; cyclic esters with high dielectric constants such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; mixed solvents of chain esters and cyclic esters; and the like. In particular, a mixed solvent of a chain ester as the main solvent and a cyclic ester is suitable.
[0092] Examples of electrolyte salts that can be dissolved in an organic solvent to prepare a non-aqueous electrolyte include LiPF6, LiBF4, LiAsF6, LiSbF6, LiCF3SO3, LiC4F9SO3, LiCF3CO2, Li2C2F4(SO3)2, LiC n F 2n+1SO3(n≧2), LiN(RfSO2)(Rf'SO2), LiC(RfSO2)3, LiN(RfOSO2)2 (where Rf and Rf' are fluoroalkyl groups), etc. may be used alone or in combination. The concentration of the electrolyte salt in the nonaqueous electrolyte is not particularly limited, but is preferably 0.3 mol / l or more, more preferably 0.4 mol / l or more, and is preferably 1.7 mol / l or less, more preferably 1.5 mol / l or less.
[0093] As the nonaqueous electrolyte of the flat nonaqueous electrolyte battery, in addition to the nonaqueous electrolyte solution, a gel electrolyte obtained by gelling the nonaqueous electrolyte solution with a gelling agent made of a polymer or the like can also be used.
[0094] (Laminated electrode body) The positive electrode and the negative electrode are stacked with a solid electrolyte layer or a separator interposed therebetween to form a stacked electrode assembly, which is used in the battery.
[0095] When forming a laminated electrode body having a solid electrolyte layer, it is preferable to pressure mold the positive electrode, negative electrode, and solid electrolyte layer in a laminated state, from the viewpoint of increasing the mechanical strength of the laminated electrode body.
[0096] (Exterior body) The exterior body of the flat nonaqueous electrolyte battery has an exterior can and a sealed can. As described above, in the flat nonaqueous electrolyte battery 1 shown in Fig. 1, the positive electrode can is the exterior can and the negative electrode can is the sealed can, but the negative electrode can may be the exterior can and the positive electrode can may be the sealed can.
[0097] As shown in FIG. 1, examples of the exterior body include an exterior can and a sealing can that are crimped and sealed with a gasket, and an exterior can and a sealing can that are bonded with a resin.
[0098] The outer can and the sealing can can be made of stainless steel or the like. The gasket can be made of polypropylene, nylon, or other materials. If heat resistance is required for the battery's intended use, heat-resistant resins with melting points exceeding 240°C, such as fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK), can also be used. If the battery is used in an application that requires heat resistance, a glass hermetic seal can be used for the sealing.
[0099] The shape of the exterior body of the flat nonaqueous electrolyte battery in a plan view may be circular or polygonal such as a quadrangle (square or rectangle), and if polygonal, the corners may be curved.
[0100] The flat nonaqueous electrolyte battery of the present invention can be used in the same applications as conventionally known flat nonaqueous electrolyte batteries (primary batteries or secondary batteries). EXAMPLES
[0101] The present invention will be described in detail below based on examples, but the present invention is not limited to the following examples.
[0102] Example 1 <Preparation of positive electrode> A positive electrode mixture was prepared by mixing Ag2S (positive electrode active material) and a sulfide-based solid electrolyte (Li6PS5Cl) in a volume ratio of 1:1. 152 mg of this positive electrode mixture was placed in a powder molding die with a diameter of 7.4 mm and compressed to 4 tonf / cm using a press. 2 The mixture was molded under a pressure of 1000 MPa to prepare a positive electrode mixture compact having a cylindrical shape.
[0103] <Formation of solid electrolyte layer> On top of the positive electrode in the powder molding die, 30 mg of the same sulfide-based solid electrolyte as that used for the positive electrode was placed, and a pressure of 1 tonf / cm was applied using a press. 2 The positive electrode mixture compact was molded under a pressure of 1000 MPa to form a solid electrolyte layer on the positive electrode mixture compact, thereby producing a laminate of the positive electrode and the solid electrolyte.
[0104] <Preparation of negative electrode> A metallic lithium foil having a thickness of 450 μm was cut into a circle to prepare a negative electrode.
[0105] <Battery assembly> The negative electrode was placed on the inner bottom surface of a stainless steel sealed can (negative electrode can) fitted with a polypropylene ring gasket. Next, the laminate of the positive electrode and solid electrolyte was stacked so that the solid electrolyte layer was on the negative electrode side, and carbon paper (carbon sheet, Toyo Tanso Co., Ltd. "PF-10HP", thickness 100 μm) punched to the same size as the positive electrode was placed on top of it as a conductive layer mainly composed of carbon, and a wave washer (metal member with elastic part, Misumi Co., Ltd. "PACK-WVWS-V5-D7") was placed on top of that, and then a stainless steel outer can (positive electrode can) was placed on top of it, and the open end of the outer can was crimped inward to seal it, forming a laminated electrode body consisting of the positive electrode, solid electrolyte layer, and negative electrode, and a flat nonaqueous electrolyte battery (solid electrolyte primary battery) with a diameter of about 9 mm was produced in which the wave washer (metal member with elastic part) and carbon paper (conductive layer mainly composed of carbon) were placed between the inner surface of the outer can and the laminated electrode body.
[0106] Example 2 A flat nonaqueous electrolyte battery was fabricated in the same manner as in Example 1, except that the metal member having the elastic portion was changed to a leaf spring ("SSRBN8-B" manufactured by Misumi Corporation).
[0107] Example 3 A flat nonaqueous electrolyte battery was fabricated in the same manner as in Example 1, except that the metal member having the elastic portion was changed to a wheel stopper (manufactured by Ochiai Corporation, "CSTW-3-SUS").
[0108] Comparative Example 1 A flat nonaqueous electrolyte battery was produced in the same manner as in Example 1, except that the wave washer was not used.
[0109] Comparative Example 2 A flat nonaqueous electrolyte battery was produced in the same manner as in Example 1, except that no wave washer was used and stainless steel (SUS) foil (thickness: 10 μm) was used instead of carbon paper.
[0110] Comparative Example 3 A flat nonaqueous electrolyte battery was produced in the same manner as in Example 1, except that SUS foil (thickness: 10 μm) was used instead of the carbon paper.
[0111] The flat nonaqueous electrolyte batteries of Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to the following evaluations.
[0112] [Internal resistance measurement] Five batteries each of Examples 1 to 3 and Comparative Examples 1 to 3 were prepared, and the internal resistance at 20° C. was measured at a frequency of 1 kHz by an AC impedance method, and the average value was calculated as the internal resistance of each battery.
[0113] [Discharge capacity measurement] The batteries of Examples 1 to 3 and Comparative Examples 1 to 3 were discharged at a constant current of 0.1 mA, and the discharge capacity until the battery voltage decreased to 0 V was measured.
[0114] The above evaluation results, together with the structure between the positive electrode can and the laminated electrode body, are shown in Table 1. In Table 1, the measurement results of internal resistance and discharge capacity are all shown as relative values when the result of Comparative Example 1 is set to 100.
[0115] [Table 1]
[0116] As shown in Table 1, the flat nonaqueous electrolyte batteries of Examples 1 to 3, in which a metal member having an elastic portion and a conductive layer mainly composed of carbon were sequentially arranged between the positive electrode can and the laminated electrode body from the positive electrode can side, had lower internal resistance and larger discharge capacity than the battery of Comparative Example 1, in which only a conductive layer mainly composed of carbon was arranged without using a metal member having an elastic portion.
[0117] The battery of Comparative Example 2, which did not use a metal member having an elastic portion and used SUS foil instead of the conductive layer mainly composed of carbon, and the battery of Comparative Example 3, which used SUS foil instead of the conductive layer mainly composed of carbon, had high internal resistance and very small discharge capacity. When these batteries were disassembled after discharge, cracks were found in the positive electrode.
[0118] Example 4 A flat nonaqueous electrolyte battery (solid electrolyte primary battery) was fabricated in the same manner as in Example 1, except that the positive electrode active material was changed to NiO2 and the amount of positive electrode mixture used was changed to 141 mg.
[0119] Comparative Example 4 A flat nonaqueous electrolyte battery was produced in the same manner as in Example 4, except that the wave washer was not used.
[0120] For the flat nonaqueous electrolyte batteries of Example 4 and Comparative Example 4, internal resistance and discharge capacity were measured in the same manner as for the battery of Example 1. These results are shown in Table 2 together with the configuration between the positive electrode can and the laminated electrode body. In Table 2, the measurement results of internal resistance and discharge capacity are all shown as relative values when the result of Comparative Example 4 is set to 100.
[0121] [Table 2]
[0122] As shown in Table 2, the flat nonaqueous electrolyte battery of Example 4, in which a metal member having an elastic portion and a conductive layer mainly composed of carbon were sequentially arranged between the positive electrode can and the laminated electrode body from the positive electrode can side, had a lower internal resistance and a larger discharge capacity than the battery of Comparative Example 4, in which only a conductive layer mainly composed of carbon was arranged without using a metal member having an elastic portion. [Explanation of symbols]
[0123] 1. Flat non-aqueous electrolyte battery 10 positive electrode 20 negative electrode 30 Separator or solid electrolyte layer 40 Positive electrode can 50 Anode can 60 Gasket 70 Carbon-based conductive layer 80 Metal member having elastic portion
Claims
1. A flat nonaqueous electrolyte battery including a laminated electrode assembly having a positive electrode and a negative electrode housed in an exterior body having a positive electrode can and a negative electrode can, The positive electrode has a molded body of a positive electrode mixture containing a positive electrode active material, a conductive layer that is elastically deformable and contains carbon as a main component is disposed on the positive electrode can side of the positive electrode; the conductive layer containing carbon as a main component is made of a carbon sheet, a metal member having an elastic portion disposed between the positive electrode can and the conductive layer containing carbon as a main component;
2. A flat nonaqueous electrolyte battery comprising an exterior body having a positive electrode can and a negative electrode can, and a laminated electrode body having a positive electrode and a negative electrode housed therein, The positive electrode has a molded body of a positive electrode mixture containing a positive electrode active material, a conductive layer mainly composed of carbon is disposed on the positive electrode can side of the positive electrode; the conductive layer containing carbon as a main component is formed of a porous carbon sheet made of fibrous carbon, a metal member having an elastic portion disposed between the positive electrode can and the conductive layer containing carbon as a main component;
3. 3. The flat nonaqueous electrolyte battery according to claim 1, wherein the exterior body is formed by crimping the positive electrode can and the negative electrode can via a gasket.
4. 4. The flat nonaqueous electrolyte battery according to claim 1, wherein the negative electrode comprises a molded body of a negative electrode mixture containing a negative electrode active material, a lithium sheet, or a lithium alloy sheet.
5. 5. The flat nonaqueous electrolyte battery according to claim 4, wherein the positive electrode mixture compact contains a solid electrolyte, the negative electrode is a lithium sheet or a lithium alloy sheet, and a solid electrolyte layer containing a solid electrolyte is disposed between the positive electrode and the negative electrode.
6. 6. The flat nonaqueous electrolyte battery according to claim 5, wherein the solid electrolyte contained in the positive electrode mixture compact and the solid electrolyte contained in the solid electrolyte layer are sulfide-based solid electrolytes.
7. 5. The flat nonaqueous electrolyte battery according to claim 4, wherein the positive electrode mixture compact contains a solid electrolyte, the negative electrode is a negative electrode mixture compact containing a negative electrode active material and a solid electrolyte, and a solid electrolyte layer containing a solid electrolyte is disposed between the positive electrode and the negative electrode.
8. 8. The flat nonaqueous electrolyte battery according to claim 7, wherein the solid electrolyte contained in the positive electrode mixture compact, the solid electrolyte contained in the negative electrode mixture compact, and the solid electrolyte contained in the solid electrolyte layer are sulfide-based solid electrolytes.
Citation Information
Patent Citations
Organic electrolytic solution battery
JP1986165963A
Manufacture of battery
JP1989030157A
Golf exercise apparatus
JP1994007493A
golf practice net
JP1995033376U
Lithium ion secondary battery
JP1999144761A